(untitled) (Research, Society and Development, 2021)
This scientometric study aimed to outline an overview of studies on ecotourism in the Pantanal published between 1990 and 2020. In this sense, studies published in the form of books, book chapters and scientific articles in journals were selected. Data were collected using the Web of Science, Scopus and, Science Direct databases, as well as the Google Scholar tool. We identified 36 published works on the subject. In 2020, seven studies were published, this being the year with the largest number of publications. 84% (n = 30) of the works were published in scientific journals, 8% (n = 3) in the form of book chapters and 8% (n = 3) in the form of books. Altogether, 92 authors wrote on the subject, but only 13 of them published at least two works. The highlights were C.J.R. Alho, with 4 publications, followed by R. Hoogesteijn and F. R. Tortato, with 3 each. Among the journals, Ecological Economics was the only one to present 3 articles. The most discussed topics were Ecotourism, Conservation, Biodiversity and Pantanal. Similarly, in the works’ keyword network, the words Pantanal, Conservation, Biodiversity and Tourism stood out.Finally, it is suggested that research institutions and Brazilian tourism associations should increase their partnerships to strengthen the research process on ecotourism in the Pantanal.